Rubus idaeus RiACS1 Gene Is Involved in Ethylene Synthesis and Accelerates Fruit Ripening in Solanum lycopersicum - Tiemei Li; Wenjiao Xin; Hang Zhang; Jiarong Jiang; Kunmiao Ding; Mengyu Liu; Nanyan Li; Guohui Yang (Agronomy)
Raspberry is a berry whose fruit is not tolerant to storage; breeding varieties with extended storage time and high comprehensive quality are significant for raspberries in cold regions. 1-Aminocyclopropane-1-carboxylic acid (ACC) synthase (ACS) is a limiting enzyme in the ethylene synthesis process, which plays essential roles in fruit ripening and softening in plants. In this study, the RiACS1 gene in raspberry (Rubus idaeus L.) variety ‘Polka’ was cloned. The RiACS1 gene overexpression vector was constructed and transformed into tomato plants using the Agrobacterium tumefaciens infection method to verify its function in their reproductive development. The RiACS1 gene, with a total length of 1476 bp, encoded a protein with 491 amino acids. The subcellular localization analysis of the RiACS1 protein in the tobacco transient expression system revealed that the RiACS1-GFP fusion protein was mainly located in the nucleus. Compared with the control, the flowering time and fruit color turning time of transgenic strains were advanced, and the fruit hardness was reduced. Overexpression of RiACS1 increased the activity of ACC synthase, ethylene release rate, and respiration rate during the transchromic phase. It changed the substance content, increased the content of vitamin C and anthocyanin in the fruit ripening process, and decreased the content of chlorophyll and titrable acid at the maturity stage. In addition, RiACS1 increased the relative expression levels of ethylene synthesis-related genes such as SlACS4, SlACO3, and SlACO1 in the fruit ripening process, while it decreased the expression levels of SlACS2 at the maturity stage. These results suggested that the RiACS1 gene could promote early flowering and fruit ripening in tomato plants. This study provided a basis for further modifying raspberry varieties using molecular biology techniques.